The rising challenge of Candida auris: insights into its transmission, drug resistance, and infection control strategies - Zhang, Weiming; Cao, Xiaoli; Liu, Chang; Gao, Shuo (Frontiers in Microbiology, 2025)
Candida auris (also known as Candidozyma auris) is a newly emerged pathogenic fungus that has garnered widespread attention globally, particularly in healthcare settings. Its rapid transmission, association high pathogenicity, and resistance to multiple antifungal agents have made it a significant public health challenge. C. auris commonly causes invasive infections in immunocompromised patients, and its resistance to various antifungal drugs complicates treatment strategies. This review summarizes the epidemiological characteristics, transmission routes, risk factors, and resistance mechanisms of C. auris, with a focus on its hospital transmission dynamics and environmental persistence. Additionally, we discuss current control and prevention strategies, including early detection, infection control measures, and the rational use of antifungal agents. Finally, the article looks ahead to future research directions, particularly the potential for vaccine development and immunotherapy, aiming to provide scientific insights for optimizing clinical diagnosis and treatment strategies.